مصطلح " القطع " في كتاب " معاني القرآن " للفراء مفهومه – دلالاته - عرباوي, أحمد الشايب (Revues faculté des lettres et des langues; No 9 (2011): مجلة كلية الآداب واللغات)
حاول الفراء في كتابه " معاني القرآن " أن يستعمل مصطلحات خاصة بالكوفيين تكون بديلا عن مصطلحات البصريين , من ذلك استعماله مصطلح " القطع " ويعني به في الغالب ما يعرف بـ " الحال " عند البصريين , لكن ذلك لم يمنعه من أن يستخدمه في معان أخرى .      وعلى العموم فإن مصطلح " القطع " في كتاب الفراء يمثل حالة الضبابية وعدم الإستقرار التي يعيشها المصطلح العلمي في مراحله الأولى .          Al-ferra , - in his book  The meanings  of Quaran - try to create grammatical terms specially for El-koofa and be a substitute for El basra terms  .  He used the term of   " El-Kataa" wich was the same meaning of " El – hall " , but that did not prevent him from using it in auther grammatical meanings .    In general, the term Al-kataa wich used by Al-ferra in his book ,showed a case uncertainty and turmoil lived by the scientific term in his early stages .